Preserving Cultural Narratives Through Aros Woven Fabric Crafts And The Philosophical Meaning Of Their Motifs: A Case Study Of The Baduy Indigenous Community - Nafilah, Mutiara Alia; Ramdani, Dadan; Sudarto, Sudarto (Universitas Galuh, 2025)
The study examines the role of Aros Baduy woven crafts as a means of preserving cultural stories, focusing on the philosophical meaning behind the motifs. These fabrics represent the historical values, philosophy, and identity of the community that have been passed down from generation to generation. The study uses qualitative methods with an ethnographic approach to explore how the motifs and colors in the weaving reflect the harmonious relationship between humans, nature, ancestors, and the social environment. Data was collected through observation and literature study, then analyzed using content analysis. The findings show that Aros weaving is important for cultural preservation. Its simple yet meaningful motifs and colours represent life lessons and values. Weaving is a marker of social and spiritual identity, playing a crucial role in traditional rituals. The process of passing on weaving knowledge, especially among women, ensures the continuity of these values amid modernization. Weaving is a living and dynamic tool of cultural communication, demonstrating how heritage is preserved through creative practices that are relevant to everyday life.